SERUTAN KAYU SEBAGAI BAHAN PEMBUATAN TAS WANITASERUTAN KAYU SEBAGAI BAHAN PEMBUATAN TAS WANITA - Artia Arin Gunawan, - (2018)
This creation uses wood powder as an ingredient in making art works that have been known and done for a long time. Senior art works using wood powder have been approved by the general public. Wood powder is waste produced from wood production. In senior crafts, materials or media are needed, but the materials or media usually have to be obtained by buying. By utilizing wood shavings we do not need to be bought, because it will be used by carpenters who will be released or disposed of. Hand over the wood. Three issues that will be discussed in this paper are discussing bags from wood waste, how to make the process of wood waste materials and how to visualize bags from wood waste materials. These problems can be solved by preparation steps, preparation of materials and manufacturing of tools, manufacturing processes and completion processes